Leibniz, Spinoza y la metafísica del posible - Ribeiro Ferreira, Maria Luísa (2014)
This paper begins by stating the personal contacts between Spinoza and Leibniz in letters XLV and XLVI, followed by Leibniz’s further comments on Spinoza’s work. By the analysis of different leibnizian texts we contrast both paradigms, namely in what concerns the concept of the possible, denied by Spinoza but absolutely necessary in Leibniz.